Peran Hukum Adat Dalam Penanggulangan Bencana Pandemi Dan Bencana Alam Dalam Bela Negara Guna Menjaga Kedaulatan Negara - Arief Fahmi Lubis; Parluhutan Sagala; Tetty Melina Lubis (Majelis: Jurnal Hukum Indonesia, 2025)
This study examines the efforts of National Defense carried out by referring to the management of reserve components in the form of indigenous communities in managing the pandemic and natural disasters. Many indigenous institutions have shown extraordinary abilities in responding to crises quickly and effectively. The purpose of this study is to show that local indigenous institutions play a key role in coordinating aid and reconstruction efforts. The mutual cooperation system that is deeply embedded in the indigenous social structure allows for the rapid mobilization of community resources to help victims and begin the recovery process. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research was conducted. The results of this study indicate that the integration of local wisdom in disaster mitigation also has the potential to strengthen the resilience of the community as a whole. By respecting and utilizing local knowledge, disaster mitigation efforts are not only more effective but also more accepted and supported by the local community in order to maintain state sovereignty.